Electoral responses to the increased contestation over European integration. The European Elections of 2019 and beyond. (March 2022) - van der Brug, Wouter; Gattermann, Katjana; de Vreese, Claes H.
This special issue focuses on the consequences of the heightened conflict between member states and increased politicization of European affairs for electoral politics in the European Union. In this introduction we begin by outlining three important developments that fuelled the politicization: (a) the common currency; (b) the increased pushback on the EU's open border policies; and (c) the inability of the EU to prevent democratic backsliding in some countries. We then discuss their consequences for EU elections, particularly campaigns, public opinion on Europe and voter behaviour, which are investigated against the backdrop of the 2019 European Parliament elections in the individual articles in this special issue. This introduction provides a contextual framework for these contributions and reflects upon some of its main findings.